Pre-prosthetic surgery: Mandible - Veeramalai Naidu Devaki; Kandasamy Balu; Sadashiva Balakrishnapillai Ramesh; Ramraj Jayabalan Arvind; Venkatesan (Wolters Kluwer Medknow Publications, 2012)
Pre-prosthetic surgery is that part of oral and maxillofacial surgery which restores oral function and facial form. This is concerned with surgical modification of the alveolar process and its surrounding structures to enable the fabrication of a well-fitting, comfortable, and esthetic dental prosthesis. The ultimate goal of pre-prosthetic surgery is to prepare a mouth to receive a dental prosthesis by redesigning and smoothening bony edges.